Predictors of Sudden Cardiac Arrest in Heart Failure - Rizzo, Toni (MD Conference Express, 2012)
The frequency of sudden cardiac arrest (SCA) is inversely related to left ventricular function; yet, many events occur in patients with ejection fraction >35% who are not candidates for an implanted cardioverter defibrillator. The aim of the Prediction of Arrhythmic Events with Positron Emission Tomography study [PAREPET] [Fallavollita JA et al. Contemp Clin Trials 2006] was to determine if the risk of SCA in medically treated patients with Class I—III heart failure can be predicted by the volume of denervated, hibernating, or infarcted myocardium.